Phonon spectrum and vibrational characteristics of l inear nanostructures in solid m atrices - Gospodarev, I.A.; Manzhelii, E.V.; Minakova, K.A.; Syrkin, E.S.; Feodosyev, S.B. (Хабаршы. Физика сериясы, 2015)
Nowadays, the structures with one-dimensional or quasi-one-dimensional nanoinclusions in various crystalline or amorphous matrices attract attention of researchers. Under real relations between the interactions of the atoms of embedded quasi-periodic systems with each other and with the atoms of the matrix, the features, inherent to one-dimensional systems, can appear in the quasi-particle spectra of these structures.